Adaptive Learning Using Online Learning Website (E-Learning) for Students Akademi Bisnis Lombok - Utama, Muhammad Budi; Atkiyan, Fahrul Hudatil; Zulkarnaen, Deki; Al Farisi, Moh. Salman; Syahrir, Syahrir (Abdi Masyarakat, 2025)
Digital-based learning in today's era has become a necessity to improve the quality of learning. This is due to the challenges of the times that require every educational institution to continue to innovate and develop in this digital era. The large number of students choosing online programs also poses a challenge for educational institutions to create learning that is safer, more comfortable, and more flexible. Therefore, this study analyzes the impact of using e-learning platforms at the Akademi Bisnis Lombok in supporting every lecture process, both in regular and online programs. We found that the impact of using this platform is significant and positive. This can be seen from the responses of lecturers and students who feel that this platform has helped them during the lecture process. However, on the other hand, there are still several aspects that need to be developed in the future to create a platform that can support learning needs comprehensively.